Numerical modelling of WNT/β-catenin signal pathway in characterization of EMT of colorectal carcinoma cell lines after treatment with Pt(IV) complexes. (November 2022) - Šeklić, Dragana S.; Đukić, Tijana; Milenković, Dejan; Jovanović, Milena M.; Živanović, Marko N.; Marković, Zoran; Filipović, Nenad
Highlights: Wnt/β-catenin pathway can lead cells to epithelial-mesenchymal transition (EMT). Numerical simulation is useful in estimation of EMT degree in cancer cells. Numerical model show the effectiveness of treatment on EMT suppression. Numerical modeling is more effective in characterization of cells already in EMT. Cytoplasmic β-catenin is key molecule of Wnt/β-catenin pathway for EMT. Abstract: Background and objective: Colorectal cancer (CRC) is at the top of the most common cancer types in the world, with significant mortality rates among both men and women. Deregulation of Wnt/β-catenin pathway and cell-cell junctions' components, acquisition of invasive phenotype, epithelial-mesenchymal transition (EMT) and invasion are important for development and progression of colorectal cancer. Numerical simulation presents method for estimation of the Wnt pathway via its individual components in cells, thus providing information about EMT, migratory and invasive potential. By using this numerical model, the effectiveness of treatment in EMT suppression can be assessed. Furthermore, the model can be adapted to ``every'' cell type, application time or duration of treatment can be also modified. Methods: We characterized colorectal cancer (CRC) cell lines (HCT-116, SW-480) from the aspect of EMT, via markers β-catenin and E-cadherin using numerical modeling. To confirm the numerical model, cells were treated with sublethal concentrations of platinum(IV) complexes and their ligands. We confirmed β-catenin regulated expression of mesenchymal markers: N-cadherin, Vimentin and MMP-9, and decreased E-cadherin expression. Treatment-induced changes were determined in the protein expression of tested markers and results showed cell-specific responses. Molecular docking was performed to investigate exact effects of treatments on E-cadherin and β-catenin in cell-cell junctions and individually in tested cells. Results: The application of the numerical model via β-catenin and E-cadherin (experimentally measured), is largely valid for the categorization of EMT progression in cells. This numerical modeling better characterizes cells with single cell migration, higher expression of mesenchymal markers, and advanced mesenchymal phenotype like HCT-116 cell line. The model was validated for the treatments and results show HCT-116 cells as more sensitive to applied compounds, among which ligands were more potent in reducing migration and invasiveness. Anti-migratory/invasive effects were due to increased E-cadherin, cytoplasmic β-catenin expression and suppressed mesenchymal markers. In silico methods showed higher affinity of tested chemicals towards free β-catenin, which is the key for regulation of migratory/invasive potential. Conclusions: Our study shows that, no matter individual properties of cell lines and EMT degree, de novo formation of intercellular junctions stands in the basis of anti-migratory/invasive process. Graphical abstract: Image, graphical abstract